Human capital: the link between leadership and organizational learning - Susana Pasamar; Mirta Diaz-Fernandez; Ma Dolores de La Rosa-Navarro (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose: There is some research showing that leadership behaviors could be important antecedents to learning, but knowledge is scarce on the impact of which leadership styles support exploitative and explorative learning. The purpose of this paper is to hypothesize that transformational leadership - more concerned with innovation - will encourage generalist human capital (HC), while transactional leadership - more focused on the efficiency of existing operations - will promote specialist HC. Design/methodology/approach: To test the hypotheses, the authors adopt a structural ambidexterity approach as the authors consider that organizations need units working on both types of learning. Findings: The results show the versatile role of transformational leaders, who are able to promote both types of HC and, in turn, both types of organizational learning. The authors have also found that marketing departments are more willing to explore than production departments. Originality/value: This study highlights the relevance of considering the department as a unit of analysis (structural ambidexterity approach), the significant role of transformational leaders in organizational learning and the mediating role of HC.
Keywords: 650; Leadership; Human capital; Exploration and exploitation learning